Experiments in climate governance – A systematic review of research on energy and built environment transitions. (15th December 2017) - Kivimaa, Paula; Hildén, Mikael; Huitema, Dave; Jordan, Andrew; Newig, Jens
Abstract: Experimentation has been proposed as a key way in which governance drives sustainability transitions, notably by creating space for innovative solutions to emerge. In seeking to bring greater coherence to the literatures on climate and sustainability governance experiments, this article reports on a systematic review of articles published between 2009 and 2015. Based on these results a new definition and typology of climate governance experiments is suggested. The typology distinguishes between the various purposes experiments can have, including niche creation, market creation, spatial development, and societal problem solving. It deepens the understanding of the diversity in experimenting by highlighting the salient features of different types of governance experiments. It can therefore guide future research to generate more cumulative research findings contributing to a better understanding of the role and outcomes of experiments in societal transitions. The findings also suggest that real transitions towards low-carbon and climate-resilient societies will require a systematic deliberate combination of different types of experiments. Highlights: Cases of low carbon or climate resilience experiments are systematically reviewed. Review material includes 25 peer-reviewed journal articles and 29 case studies. Four types of experiments for climate transition governance are identified. A concept of climate policy experiment is defined. Further research needs for experimentation in climate governance are highlighted.